Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

Eliminating A from the equation XcosA = Ycos(A + 2p/3) = Zcos(A + 4p/3). where p = pi Establish that xy + yz + zx = 0

Eliminating A from the equation XcosA = Ycos(A + 2p/3) = Zcos(A + 4p/3).


where p = pi
Establish that xy + yz + zx = 0

Grade:

1 Answers

Deepak Kumar
25 Points
7 years ago

First, use XcosA = Ycos(A+2p/3) to find tanA by expanding cos(A+2p/3).

Do the same considering XcosA = Zcos(A+4p/3)and then equate the two.

This way A is eliminated and you will get the desired result.

 

Thanks and Regards,
Deepak Kumar
AskIITians Faculty,
B. Tech, IIT Delhi.

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free